A determinant of state-owned enterprises profitability with an independent board of commissioners as moderation variables - Sophie Tiara Adriaty; Budi Purwanto; Wita Juwita Ermawati (University of Merdeka Malang, 2019)
Corporate governance drives the control function so that management could manage the corporate more effective. Good corporate governance could be the factor that boosts financial management to enhance profitability. This study examines the moderated effect of the independent commissioner proportion to the interaction between liquidity, capital structure, and sales growth to profitability. This study using purposive sampling technique, there are four state-owned enterprises (SOEs) which fit the criteria. The analysis method used in this research is moderated regression analysis on panel data. The results of the study show that liquidity and the proportion of independent commissioners influence the profitability of the company. SOEs needs to reduce the allocation of funds to current assets. Optimizing the performance of the SOEs board of commissioners also needs to be improved. The supervisory function carried out by the board of commissioners will affect operational activities so that managers will be more motivated to utilize current assets for operational investment and the company's current assets can be used optimally. Increasing the proportion of independent commissioners will also increase oversight of debt so that the condition of the company's capital structure can be optimized through the reduction of debt from SOEs.JEL Classification: G31, G34DOI: https://doi.org/10.26905/jkdp.v23i1.2519